Well, let's see that we can find the midpoint with this formula:
[tex](\frac{x_1+x_2}{2},\frac{y_1+y_2}{2})[/tex]
We have the midpoint and one of the endpoints so:
[tex](\frac{x_1+(-2)}{2},\frac{y_1+(-19)}{2})=(-1,-28)[/tex]
[tex](\frac{x_1-2}{2},\frac{y_1-19}{2})=(-1, -28)[/tex]
We have this now:
[tex]\frac{x_1-2}{2}=-1[/tex]
[tex]x_1-2= -1.2[/tex]
[tex]x_1-2=-2[/tex]
[tex]x_1=-2+2[/tex]
[tex]x_1=0[/tex]
[tex]\frac{y_1-19}{2}=-28[/tex]
[tex] y_1-19=-28.2[/tex]
[tex]y_1-19=-56[/tex]
[tex]y_1=-56+19[/tex]
[tex]y_1=-37[/tex]
So the pair is (0, -37)